Derivatives usage in risk management by U.S. and German non-financial firms: A comparative survey - Gordon M. Bodnar; Günther Gebhardt (Goethe University Frankfurt, Center for Financial Studies (CFS), 1998)
This paper is a comparative study of the responses to the 1995 Wharton School survey of derivative usage among US non-financial firms and a 1997 companion survey on German non-financial firms. It is not a mere comparison of the results of both studies but a comparative study, drawing a comparable subsample of firms from the US study to match the sample of German firms on both size and industry composition. We find that German firms are more likely to use derivatives than US firms, with 78% of German firms using derivatives compared to 57% of US firms. Aside from this higher overall usage, the general pattern of usage across industry and size groupings is comparable across the two countries. In both countries, foreign currency derivative usage is most common, followed closely by interest rate derivatives, with commodity derivatives a distant third. Usage rates across all three classes of derivatives are higher for German firms than US firms. In contrast to the similarities, firms in the two countries differ notably on issues such as the primary goal of hedging, their choice of instruments, and the influence of their market view when taking derivative positions. These differences appear to be driven by the greater importance of financial accounting statements in Germany than the US and stricter German corporate policies of control over derivative activities within the firm. German firms also indicate significantly less concern about derivative related issues than US firms, which appears to arise from a more basic and simple strategy for using derivatives. Finally, among the derivative non-users, German firms tend to cite reasons suggesting derivatives were not needed whereas US firms tend to cite reasons suggesting a possible role for derivatives, but a hesitation to use them for some reason.
urn:nbn:de:hebis:30-9545
Keywords: G32; 330; Hedging; exposure; derivatives; risk management